Pengaruh Rekrutmen, Seleksi Karyawan dan Kompetensi Terhadap Kinerja Karyawan di PT Indo Raya Tenaga - Syamsudin Syamsudin; Abdul Fatah; Entis Haryadi; Robidiansyah Robidiansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study is to examine the effect of recruitment, employee selection and competence on employee performance at PT. Indo Raya Tenaga. The methods used are Descriptive and Associative Quantitative Methods. The population is 115 employees. The sampling technique used by researchers is Probability Sampling of 54 employees. Data was collected using Questionnaires and Interviews. To test models and hypotheses, the spss program version 25 is used. The results showed that simultaneously Recruitment, Employee Selection and Competency had a positive and significant effect on Employee Performance Partial Recruitment, Employee Selection and Competency had a positive and significant effect on the Performance of PT. Indo Raya Tenaga. Suggestions for research and further companies must pay attention to recruitment, employee selection and competence can lead employees to successful career patterns, such as salary increases, promotions, and various other positive points in PT PT companies. Indo Raya Tenaga until it is growing